CONFIGURATION OF BALINESE AFFIXATION AND CULTURAL VALUES IN SATUA NANG BANGSING TEKEN I BELOG - Ni Putu Liana Widya Santhi; Putu Tania Riski Adistiani (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2024)
This research aims to describe the forms of Balinese language affixations and their meanings related to cultural values in the story of 'Nang Bangsing Teken I Belog'. In Balinese society, there are many folk tales that people call satua. Many Balinese satua are still alive, including the 'Nang Bangsing teken I Belog' story. There are cultural values ​​contained in the Balinese satua, it not only conveys the morals contained in the satua but also the culture. In Balinese culture, there are 3 types of language levels for a person's caste position and the language culture used in the 'Nang Bangsing teken I Belog' is very visible. In this satua, there were several words that contained affixations. Conclusively, this research shows that affixation found in the Balinese language is the most common morphological process found in word formation in Balinese. There are 3 types of affixes in Balinese in Balinese, namely suffixes, prefixes, and confixes. The author of the satua used bubu as a medium to convey the setting of the place which reflects the cultural values of people who live in water areas such as beaches, rivers or swamps. Apart from that, the use of bubu as a cultural object of strong language to describe traditional tools to catch fish and also to illustrate the feelings of empathy for the environment can also reflect cultural values that place value on social support by helping to protect aquatic ecosystems.